ATTITUDE TOWARDS THE FAIRY TALE GENRE OF FOLKLORE IN THE WORKS OF ERKIN VAHIDOV - Xajiyeva Dilfuza Adambayevna (Zeta Repository, 2023)
In this article, the works of Erkin Vahidov, based on the genre of folklore, were comparatively analyzed. Their similarities and differences were discussed. It was noted that the poet's poems depict social problems through symbolic images.